Flavon Compound from The Ethyl Acetate Extract of The Stem of Supit (Tetracera indica Merr.) - Muharni Muharni; Elfita Elfita; Riska Adillah; Heni Yohandini; Julinar Julinar (Molekul, 2018)
Tetracera indica Merr. in Musi Banyuasin, is one of the traditional medicine used by the community for the treatment of kidney stone disease and gout, but this claim is not recorded in the treatment of kidney stones and gout in Indonesia.  In this study, isolation of antioxidant compound from ethyl acetate extracts of supit (Tetracera indica) was done. The isolation was carried out through step gradient polarity extraction, and separated and purified by chromatography technique. The determination of the structure of the isolated compound was performed by spectroscopy method including UV, IR, and NMR 1D and 2D, and antoxidant activity was determined  by DPPH method.  An  active antioxidant compound was isolated from ethyl acetate extract in form of yellow solid (15 mg).  Based on spectroscopic analysis the isolated compound was 5,8-dihydroxy-7-methoxyflavone.  The compound showed strong antioxidant activity (IC50 8.25 μg/mL) higher than standard ascorbic acid (IC50 11.3 μg/mL).  This data concluded that efficacy of supit (Tetracera indica) for the treatment related to antioxidant activity (uric acid) is proven by the identification of one antioxidant compound of this plant.